Examination of behavior of lysine on methane (95%)–propane (5%) hydrate formation by the use of different impellers - Sotirios Nik. Longinos; Mahmut Parlaktuna (Journal of Petroleum Exploration and Production Technology, 2021)
Abstract Hydrate formation characteristics and hydrodynamic behavior have been investigated for mixture of methane–propane hydrate formation with pure water and with the amino acid of lysine 1.5 wt% at 24.5 bars and 2 °C. There were total 12 experiments with full and no baffle estimating the induction time, rate of hydrate formation, hydrate productivity and power consumption. The outcomes showed that radial flow experiments with radial flow have better behavior compared to mixed flow ones due to better interaction between gas and liquid. Furthermore, lysine experiments formed hydrates more quickly compared to pure water experiments showing that lysine functions as promoter and not as inhibitor. RT experiments consume more energy compared to PBT ones, while induction time is always smaller in RT experiments compared to PBT ones.